MANAJEMEN PENYIMPANAN ARSIP BERKAS PERKARA DI PENGADILAN AGAMA KABUPATEN BADUNG - Paramitha, Luh Gede Novia Satya; Haryanti, Ni Putu Premierita; Suhartika, I Putu (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2023)
The purpose of this study was to examine how the administration of case files in the religious courts of  Badung Province uses descriptive qualitative research methods. The data sources for this study are  observations, documents, and interviews with primary and secondary data sources from other sources  such as books, journals, and literary reviews. He is the informant for this survey. The data analysis  techniques used by the authors are data collection, data reduction, data presentation, and inference.  The results of this study show that due to lack of archivists, manual preservation system and lack of  SOP increase, the management of archival preservation at Badung District Court is still sub-optimal  from an archival preservation perspective. This can make restoring old archives difficult.